Penerapan Tanggung Jawab Sosial Universitas Melalui Konsep Triple Bottom Line Untuk Mendukung Universitas Yang Berkelanjutan (Studi Pada Universitas Muhammadiyah Di Sidoarjo, Surabaya Dan Gresik) - Detak Prapanca; Wisnu P. Setiyono; Aisha Hanif (Benefit: Jurnal Manajemen dan Bisnis, 2020)
The implementation of sustainable development is the responsibility of every level of society, one of which is the university as part of educational institutions in the community. In carrying out its business activities, the university is not only concerned with profit, but also concerned with environmental preservation and the surrounding community. So that sustainable development (sustainable development) can meet the essential needs of the present without having to sacrifice natural resources for future generations. This study aims to find out how the impact of the application of the University's Social Responsibility Implementation Through the Triple Bottom Line Concept to support Sustainable Universities and to find out how the Triple Bottom Line concept in the Universirt Social Responsibility to support sustainable development (Sustainable Development). This type of research is a qualitative approach. This study took place at the Muhammadiyah University of Sidoarjo, Muhammadiyah University of Surabaya and Muhammadiyah University Gresik. This research uses primary data and secondary data. Data analysis and interpretation is done by reducing data, presenting data, interpreting data and drawing conclusions. The results of this study are Muhammadiyah Universities in Sidoarjo, Surabaya and Gresik that have applied the triple bottom line concept in the implementation of university social responsibility (USR) activities in order to achieve sustainable development.